Site-independently integrated transgenes in the elite restorer rice line Minghui 63 allow removal of a selectable marker from the gene of interest by self-segregation - Tu, Jumin; Datta, Karabi; Oliva, Norman; Zhang, Guoan; Xu, Caiguo; Khush, Gurdev Singh; Zhang, Qifa; Datta, Swapan K. (Wiley, 2003)
In this study, we have demonstrated that two independent loci are involved in the integration of the insecticidal protein gene cryIAb/cryIAc and selectable marker gene hph in the recipient genome of the elite Chinese CMS restorer line Minghui 63. We have also documented the structural organization of these transgenes in each locus by restriction enzyme digestion and Southern blot analysis. The independent locus integration of different transgenes allowed us to remove the selectable marker gene hph from the gene of interest simply by self‐segregation. Not having the selectable marker gene will enhance the commercial value of our transgenic line TT51‐1, which showed a consistently high level of resistance against repeated infestations of yellow stem borers and natural outbreaks of leaf‐folders, without a reduction in yield potential.